Optimization of handouts for rolling stock rotations. (August 2019) - Borndörfer, Ralf; Grimm, Boris; Reuther, Markus; Schlechte, Thomas
Abstract: A railway operator creates (rolling stock) rotations in order to have a precise master plan for the operation of a timetable by railway vehicles. A rotation is considered as a cycle that multiply traverses a set of operational days while covering trips of the timetable. As it is well known, the proper creation of rolling stock rotations by, e.g., optimization algorithms is challenging and still a topical research subject. Nevertheless, we study a completely different but strongly related question in this paper, i.e.: How to visualize a rotation? For this purpose, we introduce a basic handout concept, which directly leads to the visualization, i.e., handout of a rotation. In our industrial application at DB Fernverkehr AG, the handout is exactly as important as the rotation itself. Moreover, it turns out that also other European railway operators use exactly the same methodology (but not terminology). Since a rotation can have many handouts of different quality, we show how to compute optimal ones through an integer program (IP) by standard software. In addition, a construction as well as an improvement heuristic are presented. Our computational results show that the heuristics are a very reliable standalone approach to quickly find near-optimal and even optimal handouts. The efficiency of the heuristics is shown via a computational comparison to the IP approach. Highlights: Visualizations of optimized rolling stock rotations are essential to bring them into practice. Railway planner do not accept (optimal) rotations with poor visualizations. Heuristics are able to compute near optimal visualizations in practice. Near optimal visualizations are sufficient to let planners accept a rotation.